Proposed new interior design scheme of Purple Cane Tea House and Tea Art Centre at No.11, Jalan Sultan Azlan Shah, 30100 Ipoh, Perak for Purple Cane Enterprise Sdn.Bhd./ Noorazlina Saramali - Saramali, Noorazlina (Faculty of Architecture, Planning and Surveying, 2012)
The final year project for INA316 Interior Design is about to propose new interior design of Purple Cane Tea House And Tea Art Centre at no. 11, Jalan Sultan Azlan Shah, 30100 Ipoh, Perak For Purple Cane Enterprise Sdn.Bhd. The reasearch aim for this project is to propose a whole new concept for Purple Cane Tea House and Tea Art Centre. The objectives is to promote this brand to the public that are not familiar with Chinese tea. The research methodology used in this project going through three phases to get the proposal to be done successfully. The analysis on proposed site and building has been done to give more understanding before the design process start. The case study also very helpful in designing the space planning and to understand more on the working system in a restaurant. The design concept for this project is the ‘ Diffusion of Tea ‘ with the style of Chinese old ship. There are few problems in the existing site which involve in the space planning, ventilation system and opening area. In the existing site, the tea house area and tea art centre which is the retail area are combined. Based on the case study that has been done, the tea house and the retail area are not combined. So it will not disturbed the traffic flow for the customers that come only to enjoy the environment and the tea. To solve the design problems on the space planning, the area of tea house and the retail are not combine. The display area will have its own space and have the unique design to attract the customer to buy the product.